If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -45 = 13x + 20 Reorder the terms: -45 + 5x = 13x + 20 Reorder the terms: -45 + 5x = 20 + 13x Solving -45 + 5x = 20 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. -45 + 5x + -13x = 20 + 13x + -13x Combine like terms: 5x + -13x = -8x -45 + -8x = 20 + 13x + -13x Combine like terms: 13x + -13x = 0 -45 + -8x = 20 + 0 -45 + -8x = 20 Add '45' to each side of the equation. -45 + 45 + -8x = 20 + 45 Combine like terms: -45 + 45 = 0 0 + -8x = 20 + 45 -8x = 20 + 45 Combine like terms: 20 + 45 = 65 -8x = 65 Divide each side by '-8'. x = -8.125 Simplifying x = -8.125
| -[-2(-1+m)]=-3(-1+m) | | 225=120^2/s | | 9/x-2=5/x^2 | | 7n+2=24 | | 276=115^2/x | | 5/(3p)+2/3=(5+p)/(2p) | | N=w(1+QD) | | Not=w(1+QD) | | f(x)=4x^2+16x+2 | | 96-94y=0 | | 14n+12=5n-6 | | 33-2(7r+9)=-9-6r | | D=w(1+Qn) | | 33-3(7r+9)=-9-6r | | x^3-7x^2+2x-14= | | 9x-y-3=0 | | 3a-15=42 | | -16m^2+25=0 | | f(6)=36+1.531 | | f(6)=36+.1531 | | 2n+6=17 | | y=sw-st^3 | | y=4-3*-5 | | y=-20+10 | | 14+-3p=-20 | | 9p^2=747 | | (x+2)(x-3)=(x+9)(x-4) | | 0=-16t+38.8+3 | | (x+10)= | | 69-3x=7x-19 | | y=-8+8 | | x^2-7=44 |